STUDENTS’ PERCEPTION OF USING SONG ON SPOTIFY FOR LEARNING ENGLISH - Arin Nuraeni; Silih Warni (PROJECT (Professional Journal of English Education), 2023)
Spotify has grown to become one among the most well-known streaming platforms. As a result, this research is critical in order to understand students' perspectives on utilizing Spotify tracks as an English learning medium, as well as whether students agree Spotify can be used to learn English listening skill. In this study, the researchers used the quantitative descriptive method. The researcher employed a questionnaire with 20 items in this investigation. The data for this study came in the form of the number of participants who chose each option in each questionnaire item. This study included 100 students who used the Spotify app as part of their learning. The study's findings reveal four indicators: students' habitual use of the Spotify application, the influence of Spotify on academic accomplishments, the impact of Spotify on developing English listening abilities, and the impact of using Spotify as a fun activity.